Pembelajaran Akhlak pada Interaksi Al-Khadir AS dan Musa AS Perspektif Al-Qur’an (Indo-MathEdu Intellectuals Journal, 2025)
This study examines the moral learning model that can be done by establishing approaches, strategies, methods and learning techniques that occur in Al-Khadir and Musa. In implementing the learning program on the interaction of Al-Khadir and Musa, Al-Khadir did more dialogue, question and answer and example. Example turns out to have a greater influence than speech. This research is a type of qualitative research. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. This study concludes that in the process of learning morals in the interaction of Al-Khadir and Musa, there are positive and commendable values to be implemented in daily moral learning, both formal and informal. This research uses a qualitative approach and an analytical descriptive method that uses the type of literature research and maudhu'i interpretation. The results of this study found that the story of the Prophet Moses AS and the Prophet Al-Khadir AS contained in Surah Al-Kahfi [18]: 60-82 contains various wisdom about moral learning and can be implemented in daily life.